Multi-layer impact-resistant plastic plate and preparation method thereof
Through the design and process of multi-layer composite materials, the adhesion and hierarchical structure problems of multi-layer impact-resistant panels are solved, and multi-layer impact-resistant plastic panels with high energy absorption efficiency, both rigidity and toughness are realized, which have excellent impact resistance, lightweight and aesthetics.
Patent Information
- Application Number
- CN202511247495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-09-03
AI Technical Summary
Existing multi-layer impact-resistant panels have problems such as insufficient adhesion between material layers, delamination, and peeling, and it is difficult to achieve lightweight, low cost and aesthetics while maintaining excellent impact resistance.
A combination of materials such as block polypropylene, linear low-density polyethylene, and cycloolefin copolymer is used, and a multi-layer composite die co-extrusion molding and hot-pressing roller calendering are used to form an A, B, and C layer structure. Layer A is a high-toughness base, layer B is a rigid skeleton, and layer C is a high-modulus surface layer. Combined with the striped bite structure and hot embossing treatment, a close bond between the materials is achieved.
The impact strength, flexural modulus and surface gloss of the sheet are significantly improved, and the overall performance is much better than that of traditional single-layer or conventional composite structures. The impact strength reaches 100 J/m², the flexural modulus is about 1150 MPa, and the surface gloss reaches 80 GU.
Smart Images

Figure CN120716283A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and belongs to a multi-layer impact-resistant plastic plate and a preparation method thereof. Background Art
[0002] Impact-resistant plastic materials are increasingly used in modern industry, particularly in applications such as automotive, aerospace, construction, and protective equipment, where high strength and toughness are crucial. These materials are becoming a key component, effectively resisting external impacts, preventing cracking and deformation, and thus providing reliable protection. However, the impact resistance and durability of a single material often fall short of meeting the demands of complex applications. Therefore, multi-layer composite structures are a key area of research and development.
[0003] Traditional impact-resistant panels are often made of single-layer materials (such as engineering plastics like polycarbonate and polypropylene). While these materials offer some impact resistance, they often crack, break, or severely deform when subjected to high-energy impacts. Furthermore, the mechanical properties, weather resistance, and service life of a single material are limited by its inherent characteristics, making it difficult to maintain stable impact resistance over long periods of use or in harsh environments.
[0004] To address the shortcomings of single-layer impact-resistant materials, composite materials have garnered widespread attention in recent years. Multi-layer composite impact-resistant panels combine multiple materials in a specific structure, achieving synergistic effects between their properties. By properly designing the thickness, sequence, and composition of each layer, the panel's impact resistance, toughness, wear resistance, and fatigue resistance can be significantly enhanced.
[0005] Despite this, the current design of multi-layer impact-resistant panels still faces several technical challenges. For example, insufficient adhesion between material layers can lead to delamination and peeling. An irrational hierarchical design can increase the thickness and weight of the panel, compromising performance. Inconsistent thermal expansion coefficients of different materials can also easily lead to warping or delamination. Furthermore, ensuring excellent impact resistance while maintaining lightweight, low cost, and aesthetics remains a pressing technical challenge. Summary of the Invention
[0006] In order to solve the above technical problems, the present invention provides a multi-layer impact-resistant plastic plate and a preparation method thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a multi-layer impact-resistant plastic plate material, comprising: Layer A: Main component: block polypropylene, containing by weight 90-97% block polypropylene, 1-8.5% propylene elastomer, 0.1-5% glyceryl monostearate, 0.1-5% pentaerythritol, 0.1-5% triester phosphite, and 0.1-5% talc. Layer B: Mainly composed of linear low-density polyethylene and low-density polyethylene, containing 30-65% linear low-density polyethylene, 30-65% low-density polyethylene, 1-5% polyolefin elastomer, and 0.1-3% calcium stearate by weight; Layer C: mainly composed of cycloolefin copolymer or special cycloolefin copolymer, containing by weight 61.0-94.7% of cycloolefin copolymer or special cycloolefin copolymer, 5-20% of polyethylene, 0.1-9% of calcium stearate, 0.1-5% of pentaerythritol ester, and 0.1-5% of colorant; The plate is co-extruded through a single-screw or multi-screw extruder and a multi-layer composite die head, with a barrel temperature of 100-200° C. and a die head pressure of 5-19 MPa, and is calendered and shaped through a hot pressing roller at a linear pressure of 2-8 MPa.
[0008] Preferably, the A layer further comprises 1-3% of a light foaming agent.
[0009] Preferably, the block polypropylene is copolymerized with propylene and at least one α-olefin comonomer, wherein the α-olefin comonomer is selected from ethylene, 1-butene, 1-hexene, 1-octene, styrene, propylene / 1-octene copolymer, propylene / isoprene copolymer, ethylene / propylene / 1-octene terpolymer or any combination of the above copolymers; The propylene-based elastomer is a polypropylene-based elastomer obtained by copolymerizing propylene with ethylene or α-olefin.
[0010] Preferably, the B layer further comprises 10-20% of lightweight foaming agent chopped glass fibers, wherein the chopped glass fibers are of E-glass type, with a diameter of 10-20 μm and a length of 3-4 mm.
[0011] Preferably, the linear low-density polyethylene is a copolymer of ethylene and 1-butene, 1-hexene or 1-octene, wherein the copolymer has a density of 0.915-0.940 g / cm³ and a melt flow rate of 1-3 g / 10 min (190°C / 2.16 kg); The low-density polyethylene is prepared from ethylene monomer by high-pressure free radical polymerization, and the low-density polyethylene has a density of 0.910-0.925 g / cm³ and a melt flow rate of 0.2-5 g / 10 min (190°C / 2.16 kg); The polyolefin elastomer is an ethylene-octene block copolymer, wherein the ethylene content is 70-80 wt% and the octene content is 20-30 wt%. The typical Mooney viscosity of the polyolefin elastomer is 23 MU (ML1+4100°C) and the hardness is ShoreA30-90; The calcium stearate has a density of 1.03-1.12 g / cm³ and a spherical nanoparticle size of about 100-300 nm.
[0012] Preferably, the cycloolefin copolymer or special cycloolefin copolymer is a random copolymer obtained by copolymerizing a cycloolefin monomer and a linear olefin monomer; the cycloolefin monomer is selected from norbornene, 1,2,3,4,4a,5,8,8a-octahydro-1,4:5,8-bicyclo[4.4.0]octane or cyclopentene; and the linear olefin monomer is selected from ethylene, propylene or 1-octene.
[0013] Preferably, the special cycloolefin copolymer is a special cycloolefin copolymer prepared by copolymerizing a cycloolefin monomer and a comonomer containing a polar functional group.
[0014] Preferably, the plate is formed by co-extrusion or compounding of at least one functional layer, and each functional layer independently meets the following thickness limitations according to its type in the laminated structure: Type A layer (bending variability / energy absorption layer): the thickness of a single layer accounts for 50%–90% of the total thickness of the composite plate; Type B layer (high strength / energy absorption layer): the thickness of a single layer accounts for 5%–25% of the total thickness of the composite plate; Type C layer (rigid protective layer): the thickness of a single layer accounts for 1%–10% of the total thickness of the composite plate.
[0015] Preferably, the plate is formed by co-extrusion or compounding of at least one functional layer, and the position of each layer in the structure determines its main function.
[0016] Preferably, the master batches of layers A, B and C can be co-extruded and compounded in any combination of single layer, double layer or triple layer.
[0017] Preferably, a striped interlocking structure is provided at the A / B layer interface, with a stripe width of 0.5-2 mm and a spacing of 1-5 mm, and interlayer interlacing and locking is achieved through a core groove and a die outlet with a back pressure of 5-15 MPa.
[0018] Preferably, the surface C layer of the plate is hot embossed to form a micron-scale dot matrix with an embossing point diameter of 0.1-0.3 mm and a point spacing of 0.5-1 mm, a calendering line pressure of 2-8 MPa, and a calendering temperature of 120-160°C.
[0019] The present invention also provides a method for preparing the multi-layer impact-resistant plastic plate, comprising the steps of: (1) Melt the A, B, and C layer masterbatches through independent feed ports respectively; (2) The melt is co-extruded through a multi-layer composite die, with a barrel temperature gradient of 100-200°C and a die pressure of 5-19 MPa; (3) The hot pressing roller group calenders the composite material at a linear pressure of 2-8 MPa; (4) Cooling, shaping, pulling and rolling to form a layered composite plate structure having at least one type of material layer among layer A, layer B and layer C.
[0020] Compared with the prior art, the present invention provides a multi-layer impact-resistant plastic plate and a preparation method thereof, which has the following beneficial effects: The present invention achieves efficient energy absorption and both rigidity and toughness of the board through precise design of the material ratio of the three layers: in layer A, about 90 wt% segmented polypropylene (PPB) is combined with 5 wt% polyolefin elastomer (POE). The POE particles first deform and absorb energy in the PPB continuous phase, and then the PPB undergoes plastic flow, greatly improving the fracture toughness; in layer B, about 50 wt% linear low-density polyethylene (LLDPE) and 45 wt% low-density polyethylene (LDPE) are used to construct a rigid skeleton, and 5 wt% POE particles are introduced to induce plastic energy dissipation at the front of the microcracks, taking into account both initial rigidity and secondary energy absorption; in layer C, about 80 wt% cyclic olefin copolymer (COC) is used to give the surface layer high modulus and scratch resistance, and 20 wt% polyethylene (PE) is combined to improve the interface toughness and good combination with layer B to achieve a smooth and high-gloss surface, so that the impact strength of the board reaches 100 J / m² and the flexural modulus is about 1150 MPa, and the surface gloss reaches 80GU, and the comprehensive performance is much better than traditional single-layer or conventional composite structures.
[0021] The features and advantages of the present invention will be described in detail through embodiments with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic structural diagram of a five-layer structural plate according to Example 1 of the present invention. DETAILED DESCRIPTION
[0023] To make the objectives, technical solutions, and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and examples. However, it should be understood that the specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the scope of the present invention. In addition, in the following description, descriptions of well-known structures and technologies are omitted to avoid unnecessary confusion of the present invention.
[0024] Unless otherwise specified, all reagents used in the examples are commercially available reagents or raw materials. Unless otherwise specified, the test methods used in the examples are conventional methods in the art. The mechanical properties of the composite materials were tested using the following methods: impact strength was measured according to GB / T 1843-2008, flexural modulus was measured according to GB / T 9341-2008, surface gloss was measured according to GB / T 8807-1988, and peel strength was measured according to ISO 11339:2022.
[0025] The present invention provides a multi-layer impact-resistant plastic plate material, comprising: Layer A: Mainly composed of segmented polypropylene (PPB), containing by weight 90-97% segmented polypropylene (PPB), 1-8.5% propylene elastomer (PBE), 0.1-5% glyceryl monostearate (GMS), 0.1-5% pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate), 0.1-5% tris(2,4-di-tert-butylphenyl) phosphite, and 0.1-5% talc. Layer B: Mainly composed of linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE), containing by weight 30-65% linear low-density polyethylene (LLDPE), 30-65% low-density polyethylene (LDPE), 1-5% polyolefin elastomer (POE), and 0.1-3% calcium stearate; Layer C: mainly composed of cyclic olefin copolymer (COC) or special cyclic olefin copolymer (SOOC), containing by weight 61.0-94.7% of cyclic olefin copolymer (COC) or special cyclic olefin copolymer (SOOC), 5-20% of polyethylene (PE), 0.1-9% of calcium stearate (Ca-St), 0.1-5% of pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate), and 0.1-5% of colorant; The plate is co-extruded through a single-screw or multi-screw extruder and a multi-layer composite die head, with a barrel temperature of 100-200° C. and a die head pressure of 5-19 MPa, and is calendered and shaped through a hot pressing roller at a linear pressure of 2-8 MPa.
[0026] Preferably, the A layer further comprises 1-3% of a light foaming agent.
[0027] Preferably, the block polypropylene is copolymerized with propylene and at least one α-olefin comonomer, wherein the α-olefin comonomer is selected from ethylene, 1-butene, 1-hexene, 1-octene, styrene, propylene / 1-octene copolymer, propylene / isoprene copolymer, ethylene / propylene / 1-octene terpolymer or any combination of the above copolymers; The propylene-based elastomer is a polypropylene-based elastomer obtained by copolymerizing propylene with ethylene or α-olefin.
[0028] Preferably, the B layer further comprises 10-20% of lightweight foaming agent chopped glass fibers, wherein the chopped glass fibers are of E-glass type, with a diameter of 10-20 μm and a length of 3-4 mm.
[0029] Preferably, the linear low-density polyethylene is a copolymer of ethylene and 1-butene, 1-hexene or 1-octene, and the copolymer has a density of 0.915-0.940 g / cm³ and a melt flow rate of 1-3 g / 10 min (190°C / 2.16 kg); The low-density polyethylene is prepared from ethylene monomer by high-pressure free radical polymerization, and the low-density polyethylene has a density of 0.910-0.925 g / cm³ and a melt flow rate of 0.2-5 g / 10 min (190°C / 2.16 kg); The polyolefin elastomer is an ethylene-octene block copolymer, wherein the ethylene content is 70-80 wt% and the octene content is 20-30 wt%. The typical Mooney viscosity of the polyolefin elastomer is 23 MU (ML1+4100°C) and the hardness is ShoreA30-90; The calcium stearate has a density of 1.03-1.12 g / cm³ and a spherical nanoparticle size of about 100-300 nm.
[0030] Preferably, the cycloolefin copolymer or special cycloolefin copolymer is a random copolymer obtained by copolymerizing a cycloolefin monomer and a linear olefin monomer; the cycloolefin monomer is selected from norbornene, 1,2,3,4,4a,5,8,8a-octahydro-1,4:5,8-bicyclo[4.4.0]octane or cyclopentene; and the linear olefin monomer is selected from ethylene, propylene or 1-octene.
[0031] Preferably, the special cycloolefin copolymer is a special cycloolefin copolymer prepared by copolymerizing a cycloolefin monomer and a comonomer containing a polar functional group.
[0032] Preferably, the plate is formed by co-extrusion or compounding of at least one functional layer, and each functional layer independently meets the following thickness limitations according to its type in the stacked structure: Type A layer (bending variability / energy absorption layer): the thickness of a single layer accounts for 50%–90% of the total thickness of the composite plate; Type B layer (high strength / energy absorption layer): the thickness of a single layer accounts for 5%–25% of the total thickness of the composite plate; Type C layer (rigid protective layer): the thickness of a single layer accounts for 1%–10% of the total thickness of the composite plate.
[0033] Preferably, the board is formed by co-extrusion or compounding of at least one functional layer, and the position of each layer in the structure determines its main function.
[0034] Preferably, the master batches of layers A, B and C can be co-extruded and compounded in any combination of single layer, double layer or triple layer.
[0035] Preferably, a striped interlocking structure is provided at the A / B layer interface, with a stripe width of 0.5-2 mm and a spacing of 1-5 mm, and interlayer interlacing and locking is achieved through a core groove and a die outlet with a back pressure of 5-15 MPa.
[0036] Preferably, the surface C layer of the sheet material is hot embossed to form a micron-scale dot matrix with an embossing point diameter of 0.1-0.3 mm and a point spacing of 0.5-1 mm, a calendering line pressure of 2-8 MPa, and a calendering temperature of 120-160°C.
[0037] The present invention also provides a method for preparing the multi-layer impact-resistant plastic plate, comprising the steps of: (1) Melt the A, B, and C layer masterbatches through independent feed ports respectively; (2) The melt is co-extruded through a multi-layer composite die, with a barrel temperature gradient of 100-200°C and a die pressure of 5-19 MPa; (3) The hot pressing roller group calenders the composite material at a linear pressure of 2-8 MPa; (4) Cooling, shaping, pulling and rolling to form a layered composite plate structure having at least one type of material layer among layer A, layer B and layer C.
[0038] Specifically, the A-layer formula is designed to construct a high-toughness substrate, forming a rigid-toughness gradient with the rigid outer layer: POE can be dispersed in the PPB continuous phase in the form of nano / micron-sized particles, and first undergoes elastic deformation under stress to absorb impact energy, and then the PPB phase undergoes plastic deformation, significantly improving the fracture toughness; GMS, as an internal lubricant, can improve the lubricity of the PPB / POE phase interface, promote melt flow and molding, and at the same time, a trace amount of GMS forms a lubricating layer at the interface to alleviate the effect of stress concentration.
[0039] The LDPE in layer B has a high yield elongation, allowing it to withstand significant deformation energy under macroscopic loading. LDPE provides morphological stability and initial stiffness, and the combination of the two forms a broad-spectrum energy dissipation platform. POE forms a dispersed phase within the PE matrix. When microcracks form, the POE particles induce plastic flow and hinder crack propagation, significantly improving impact strength. (Optional) The chopped glass fibers are E-glass, approximately 10–20 μm in diameter and 3–4 mm in length. They are treated with a silane coupling agent and dispersed within the matrix to enhance stiffness and crack-bridging capabilities.
[0040] The COC and SOOC materials in the C layer have a high glass transition temperature and are very suitable as a rigid surface layer. They exhibit high flexural modulus and excellent surface flatness at room temperature. 5–20wt% PE improves the toughness of COC and enhances the interfacial adhesion with the B layer. A uniform transition zone is formed through melt co-extrusion, reducing interfacial stress concentration.
[0041] During the production process, three different functional masterbatches were selected as raw materials based on product design requirements: low-density polyethylene masterbatch (for impact resistance), segmented polypropylene masterbatch (for flexural strength), and cyclic olefin copolymer masterbatch (for strength and surface gloss). These masterbatches were pre-treated before use to ensure uniform particle size and good flowability, meeting the requirements of subsequent production processes.
[0042] First, the three masterbatches are fed into different feed ports of a three-screw extruder. The flow rate, temperature, and feeding method of each masterbatch are precisely controlled based on its characteristics and actual needs. The structural design of the three-screw extruder enables efficient control of the melting process and promotes uniform mixing of the various raw materials.
[0043] Since different masterbatches have different melting temperatures, the temperature in each heating section of the three-screw extruder is precisely controlled according to the characteristics of each material.
[0044] In the latter section of the extruder, the molten masterbatch passes through a specially designed die to form a multilayer structure. The materials for each layer are arranged in a predetermined proportion and sequence to ensure the independence and rationality of the functions of each layer in the sheet. At this point, the masterbatch for layers A, B, and C is arranged alternately, giving the sheet different functional properties.
[0045] In the die area, the three materials are combined at high temperatures through a hot pressing process. The high-pressure extruder ensures that the different functional layers are tightly bonded under the influence of temperature and pressure, forming a stable multi-layer composite sheet. The materials are tightly bonded through molecular interactions.
[0046] The extruded sheet passes through a cooling system for rapid cooling, helping it solidify and take shape quickly. Precise control of the cooling rate and temperature is crucial during the cooling process; excessively fast or slow cooling can lead to uneven material properties or deformation. After cooling, the sheet gradually hardens, ensuring that the various functionalities are fully realized.
[0047] The cooled sheet exhibits a high gloss surface, with layer A providing excellent impact resistance, layer B providing bending resistance, and layer C imparting high strength and surface gloss to the overall sheet. This preparation method effectively achieves a three-functional material composite, ensuring the multi-layer sheet's superior performance in strength, toughness, and gloss.
[0048] Description of the raw materials used in the embodiments of the present invention: A layer masterbatch: PPB: M02D-G, propylene / 1-octene random copolymer, MFR≈26 g / 10 min; Supplier: Sinopec Yangzi Petrochemical Co., Ltd. PBE: Vistamaxx™ series, a polypropylene-based elastomer made by copolymerizing propylene with ethylene or other α-olefins, Mooney ≈ 23 MU; Supplier: ExxonMobil; GMS: glyceryl monostearate; Supplier: Changzhou Kesai Chemical; Pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate): Irganox® 1010 pentaerythritol ester antioxidant, supplier: BASF; Tris(2,4-di-tert-butylphenyl) phosphite: P-168, supplier: Yashi; Nano talc powder: particle size <1μm; supplier: Shanghai Sanmei; Foaming agent: Azodicarbonamide; Supplier: Haili Chemical.
[0049] B layer masterbatch: LLDPE: 7050HJ, supplier: Sinopec Zhenhai Refining and Chemical Co., Ltd. LDPE: ZH220 (MFR≈2 g / 10 min), supplier: China Petrochemical Corporation; POE: AFFINITY™ GA1900 (Mooney ≈ 23 MU; Shore A 30–90), supplier: Dow Chemical; Ca-St: Spherical nano calcium stearate: Hydrobrite™ 850; Supplier: Milliken&Co.; Chopped glass fiber: Advantex® 9703, E-glass chopped glass fiber, supplier: OwensCorning Composites; C layer masterbatch: COC: OPAS® COC, supplier: POLYPLASTICS CO., LTD. PE: HDPE:LLDPE = 1:1, supplier: Dowlex™ / Sinopec Zhenhai; Ca-St: Hydrobrite™ 850; Pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate): Irganox® 1010; Colorant: RTP masterbatch.
[0050] Example 1 Five-layer structural board 1. Raw materials and ingredients A-layer masterbatch: PPB: 2.79 kg, PBE: 0.06 kg, GMS: 0.0225 kg; Pentaerythritol ester antioxidant: 0.0225 kg; Tris(2,4-di-tert-butylphenyl) phosphite: 0.0225 kg; Talc: 0.0225 kg; Foaming agent: 0.06 kg; B layer masterbatch: 2.0 kg of LLDPE (melting point ≈ 120 °C, MFR 2.16 g / 10 min); 2.0 kg of LDPE (MFR ≈ 2 g / 10 min); 0.1 kg of POE (Mooney ≈ 23 MU; Shore A 30–90); 0.02 kg of spherical nano-calcium stearate (particle size ≈ 200 nm); and 0.8 kg of E-glass chopped glass fibers (diameter ≈ 13 μm, length 3–4 mm). C layer masterbatch: COC (Tg≈138°C, density≈1.02 g / cm³) 2.0 kg; PE 0.5 kg; Ca-St: 0.03 kg; Pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate): 0.02 kg; colorant 0.1 kg.
[0051] 2. Secondary granulation process Drying: A / C layer was vacuum dried at 80℃ for 4 h; B layer of glass fiber and Ca–St was dried at 100℃ for 2 h.
[0052] Mixing: Mix the raw materials of each layer according to the ratio (Layer A: PPB 90–97%, POE 1–8.5%, and the total amount of other additives not exceeding 10%; Layer B: LLDPE 30–55%, LDPE 30–60%, POE 1–9%, Ca–St 0.1–3%, and glass fiber 10–20%; Layer C: COC61–94.7%, PE 5–20%, Ca–St 0.1–9%, and the total amount of antioxidants and masterbatch not exceeding 10%) and stir for 5 min.
[0053] Twin-screw extrusion: Layer A: 150 / 155 / 160 / 165°C, die head 160°C, screw 200 rpm; Layer B: 130 / 140 / 150 / 155°C, die 155°C, screw 180 rpm; C layer: 150 / 160 / 170 / 175°C, die 175°C, screw 160 rpm; Underwater pelletizing, and drying at 60 ℃ for 2 h after pelletizing.
[0054] 3. Five-layer co-extrusion molding and shaping Three-screw extruder: barrel 140–165 °C, die 165 °C, screw 150 rpm; feed sequence A / B / C.
[0055] The co-extrusion die head forms an A / B / C / B / A five-layer structure; the hot pressing roller group (140℃, 5 MPa) is used for calendering and shaping; and the water-cooled roller is cooled to ~25℃ for winding.
[0056] 4. Product structure and performance Thickness: 1.5 mm (C / B / A / B / C = 0.1 / 0.2 / 0.9 / 0.2 / 0.1 mm); Impact strength: 105 J / m² (GB / T 1843-2008), significantly higher than conventional three-layer PP / PE composite panels (approximately 50–70 J / m²); Flexural modulus: 1200 MPa; Surface gloss: 85 GU; Gardner good scratch resistance; Peel strength: 5.1 N / mm.
[0057] Example 2: Three-layer structural board 1. Raw materials and ingredients Layer A masterbatch: PPB: 1.5 kg; POE: 0.1 kg; GMS: 0.05 kg; Pentaerythritol Tetrakis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate): 0.05 kg; Tris(2,4-di-tert-butylphenyl) phosphite: 0.05 kg; Talc: 0.05 kg; Layer B masterbatch: LLDPE: 1.5 kg; LDPE: 1.0 kg; POE: 0.05 kg; Ca–St: 0.02 kg C layer masterbatch: COC: 1.0 kg; PE: 0.3 kg; pentaerythritol ester antioxidant: 0.02 kg; colorant: 0.03 kg.
[0058] 2. Secondary granulation process Drying: Same as Example 1; Mixing: Stir separately for 5 min; Granulation parameters: A layer: 150 / 155 / 160 / 165°C, 160°C, 200 rpm; B layer: 130 / 140 / 150 / 155°C, 155°C, 180 rpm; C layer: 150 / 160 / 170 / 175°C, 175°C, 160 rpm; Pelletized underwater and dried at 60 °C for 2 h.
[0059] 3. Three-layer co-extrusion molding and shaping Triple-screw extrusion: 140–165 °C, 165 °C, 150 rpm; A / B / C sequential co-extrusion; hot pressing rollers 140°C, 5 MPa; water-cooled winding.
[0060] 4. Product structure and performance Thickness: 1.2 mm (A / B / C = 0.8 / 0.3 / 0.1 mm); Impact strength: 110 J / m², flexural modulus: 1150 MPa, surface gloss: 80 GU, peel strength: 5.3 N / mm.
[0061] Example 3: Double-layer structure board 1. Raw materials and ingredients Layer B masterbatch: LLDPE: 3.0 kg; LDPE: 1.0 kg; Ca–St: 0.1 kg; E-glass chopped glass fiber: 0.5 kg; C layer masterbatch: COC: 2.0 kg; PE: 0.6 kg; pentaerythritol ester antioxidant: 0.04 kg; colorant: 0.06 kg.
[0062] 2. Secondary granulation process Drying: B layer 80℃×4 h; C layer 100℃×2 h; Mixing: Stir for 5 min; Granulation: B layer: 150 / 155 / 160 / 165°C, 160°C, 200 rpm; C layer: 130 / 140 / 150 / 155°C, 155°C, 180 rpm; Pelletized underwater and dried at 60 °C for 2 h.
[0063] 3. Double-layer co-extrusion molding and shaping Twin-screw extrusion: 135–160 °C, 160 °C, 140 rpm; Hot pressing roller: 135℃, 4 MPa; water-cooled winding.
[0064] 4. Product structure and performance Thickness: 1.0 mm (A / B = 0.5 / 0.5 mm); Impact strength: 109 J / m², flexural modulus: 1180 MPa, surface gloss: 82 GU, surface scratch resistance: no obvious scratches, peel strength: 5.2 N / mm.
[0065] Comparative Example 1: Traditional five-layer PP / PE / PP / PE / PP composite board 1. Raw material formula Surface layer: Homopolymer polypropylene (PP) masterbatch - 100 parts by weight Transition layer: Linear low-density polyethylene (LLDPE) masterbatch - 100 parts by weight Middle energy absorbing layer: homopolymer polypropylene (PP) masterbatch - 100 parts by weight Transition layer: Linear low-density polyethylene (LLDPE) masterbatch - 100 parts by weight Bottom skin layer: Homopolymer PP masterbatch - 100 parts by weight 2. Secondary granulation After drying (80°C × 3–4h), the masterbatch of each layer directly enters the co-extrusion system; 3. Co-extrusion molding and customization The five-layer die head configuration is PP / LLDPE / PP / LLDPE / PP in sequence; the rest of the process is the same as "Comparative Example 1"; 4. Product structure and performance Thickness ratio: PP / PE / PP / PE / PP = 0.2 / 0.2 / 0.7 / 0.2 / 0.2 mm, total thickness 1.5 mm; Impact strength: 90 J / m² Flexural modulus: 900 MPa Surface gloss: 75 GU Peel strength: 4.5 N / mm Comparative Example 2: Traditional three-layer PP / PE composite board 1. Raw material formula Surface layer: Homopolymer polypropylene (PP) masterbatch - 100 parts by weight Middle energy absorbing layer: linear low-density polyethylene (LLDPE) masterbatch - 100 parts by weight Bottom skin layer: Homopolymer PP masterbatch - 100 parts by weight 2. Secondary granulation After drying (80°C × 3–4h), the masterbatch of each layer directly enters the co-extrusion system; 3. Co-extrusion molding and shaping Twin-screw or triple-screw co-extrusion: The temperature range is approximately: 180–200°C (PP) / 150–170°C (PE), and the screw speed is approximately 150–200 rpm; Die head and hot pressing roller: The die head is set to a three-layer structure, with PP surface and bottom layers and LLDPE in the center; The temperature of the hot pressing roller is about 150–160°C, and the linear pressure is 3–5 MPa; Cooling system: water tank or air cooling, traction speed control to avoid warping.
[0066] 4. Product structure and performance Thickness ratio of three layers: PP:PE:PP ≈ 1:1:1, total thickness about 1.5–2.0 mm; Impact strength: 80 J / m2, flexural modulus: 950 MPa, surface gloss: 70 GU, peel strength: 3.8 N / mm.
[0067] Comparative Example 3: Traditional two-layer PP / PE composite board 1. Raw material formula Surface layer: Homopolymer polypropylene (PP) masterbatch - 100 parts by weight Bottom energy absorbing layer: Linear low-density polyethylene (LLDPE) masterbatch - 100 parts by weight 2. Secondary granulation After drying (80 °C × 3–4 h), the masterbatch of each layer directly enters the coextrusion system; 3. Co-extrusion molding and shaping Twin-screw co-extrusion: temperature range 180–200°C (PP) / 150–170°C (PE), screw speed 150 rpm; Die head: two-layer structure, PP / LLDPE; Hot pressing roller: 150℃, 3 MPa; water-cooled winding; 4. Product structure and performance Thickness ratio: PP: PE = 0.5: 1.0 mm, total thickness 1.5 mm; Impact strength: 70 J / m² Flexural modulus: 800 MPa Surface gloss: 65 GU Peel strength: 2.5 N / mm The above is a detailed description of the multi-layer impact-resistant plastic sheet, preparation method, and preparation process provided by the embodiments of the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the examples is only intended to help understand the methods and core concepts of the present invention. The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.
[0068] Table 1. Mechanical properties test data of various embodiments and comparative examples The following conclusions can be drawn from the test data in Table 1: From the corresponding comparison of Example 1 (five layers), Example 2 (three layers), Example 3 (two layers) and Comparative Example 1 (five layers), Comparative Example 2 (three layers), Comparative Example 3 (two layers), it can be concluded that: compared with the common plastic sheets in the prior art, the multi-layer impact-resistant plastic sheet prepared by the present invention has significantly higher strength, toughness, glossiness and peeling strength.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A multi-layer impact-resistant plastic sheet, characterized in that: include: Layer A: Main component: block polypropylene, containing by weight 90-97% block polypropylene, 1-8.5% propylene elastomer, 0.1-5% glyceryl monostearate, 0.1-5% pentaerythritol, 0.1-5% triester phosphite, and 0.1-5% talc. Layer B: Mainly composed of linear low-density polyethylene and low-density polyethylene, containing 30-65% linear low-density polyethylene, 30-65% low-density polyethylene, 1-5% polyolefin elastomer, and 0.1-3% calcium stearate by weight; Layer C: mainly composed of cycloolefin copolymer or special cycloolefin copolymer, containing by weight 61.0-94.7% of cycloolefin copolymer or special cycloolefin copolymer, 5-20% of polyethylene, 0.1-9% of calcium stearate, 0.1-5% of pentaerythritol ester, and 0.1-5% of colorant; The plate is co-extruded through a single-screw or multi-screw extruder and a multi-layer composite die head, with a barrel temperature of 100-200° C. and a die head pressure of 5-19 MPa, and is calendered and shaped through a hot pressing roller at a linear pressure of 2-8 MPa.
2. The multi-layer impact-resistant plastic sheet according to claim 1, characterized in that: The A layer further comprises a light foaming agent in an amount of 1-3%.
3. The multi-layer impact-resistant plastic sheet according to claim 1, characterized in that: The block polypropylene is copolymerized with propylene and at least one α-olefin comonomer, wherein the α-olefin comonomer is selected from ethylene, 1-butene, 1-hexene, 1-octene, styrene, propylene / 1-octene copolymer, propylene / isoprene copolymer, ethylene / propylene / 1-octene terpolymer or any combination of the above copolymers; The propylene-based elastomer is a polypropylene-based elastomer obtained by copolymerizing propylene with ethylene or α-olefin.
4. The multi-layer impact-resistant plastic sheet according to claim 1, wherein: The B layer further comprises 10-20% of lightweight foaming agent chopped glass fibers, wherein the chopped glass fibers are of E-glass type, with a diameter of 10-20 μm and a length of 3-4 mm.
5. The multi-layer impact-resistant plastic sheet according to claim 1, characterized in that: The linear low-density polyethylene is a copolymer of ethylene and 1-butene, 1-hexene or 1-octene, wherein the copolymer has a density of 0.915-0.940 g / cm³ and a melt flow rate of 1-3 g / 10 min (190°C / 2.16 kg); The low-density polyethylene is prepared from ethylene monomer by high-pressure free radical polymerization, and the low-density polyethylene has a density of 0.910-0.925 g / cm³ and a melt flow rate of 0.2-5 g / 10 min (190°C / 2.16 kg); The polyolefin elastomer is an ethylene-octene block copolymer, wherein the ethylene content is 70-80 wt% and the octene content is 20-30 wt%. The typical Mooney viscosity of the polyolefin elastomer is 23 MU (ML1+4100°C) and the hardness is Shore A30-90; The calcium stearate has a density of 1.03-1.12 g / cm³ and a spherical nanoparticle size of about 100-300 nm.
6. The multi-layer impact-resistant plastic sheet according to claim 1, characterized in that: The cycloolefin copolymer or special cycloolefin copolymer is a random copolymer obtained by copolymerizing a cycloolefin monomer and a linear olefin monomer; the cycloolefin monomer is selected from norbornene, 1,2,3,4,4a,5,8,8a-octahydro-1,4:5,8-bicyclo[4.4.0]octane or cyclopentene; the linear olefin monomer is selected from ethylene, propylene or 1-octene.
7. The multi-layer impact-resistant plastic sheet according to claim 1, characterized in that: The special cycloolefin copolymer is prepared by copolymerizing a cycloolefin monomer and a comonomer containing a polar functional group.
8. The multi-layer impact-resistant plastic sheet according to any one of claims 1 to 7, characterized in that: The sheet material is formed by co-extrusion or compounding of at least one functional layer, and each functional layer independently meets the following thickness limitations according to its type in the laminated structure: Type A layer: the thickness of a single layer accounts for 50%–90% of the total thickness of the composite plate; Type B layer: the thickness of a single layer accounts for 5%–25% of the total thickness of the composite plate; Type C layer: the thickness of a single layer accounts for 1%–10% of the total thickness of the composite plate.
9. The multi-layer impact-resistant plastic sheet according to any one of claims 1 to 7, characterized in that: The plate is formed by co-extrusion or compounding of at least one functional layer, and the position of each layer in the structure determines its main function.
10. The multi-layer impact-resistant plastic sheet according to any one of claims 1 to 7, characterized in that: The master batches of the A, B and C layers can be co-extruded and compounded in any combination of single layer, double layer or three layers.
11. The multi-layer impact-resistant plastic sheet according to any one of claims 1 to 7, characterized in that: The A / B layer interface is provided with a striped interlocking structure, with a stripe width of 0.5–2 mm and a spacing of 1–5 mm, and interlayer interlacing and locking is achieved through a core groove and a die outlet with a back pressure of 5–15 MPa.
12. The multi-layer impact-resistant plastic sheet according to any one of claims 1 to 7, characterized in that: The surface C layer of the plate is subjected to hot embossing treatment to form a micron-level dot matrix with an embossing point diameter of 0.1-0.3 mm and a point spacing of 0.5-1 mm. The calendering line pressure is 2-8 MPa and the calendering temperature is 120-160°C.
13. A method for preparing a multi-layer impact-resistant plastic sheet, characterized by: Including steps: (1) Melt the A, B, and C layer masterbatches through independent feed ports respectively; (2) The melt is co-extruded through a multi-layer composite die, with a barrel temperature gradient of 100-200°C and a die pressure of 5-19 MPa; (3) The hot pressing roller group calenders the composite material at a linear pressure of 2-8 MPa; (4) Cooling, shaping, pulling and rolling to form a layered composite plate structure having at least one type of material layer among layer A, layer B and layer C.
Citation Information
Patent Citations
Multilayer film and preparation method thereof
CN116674273A
Polypropylene composite material as well as preparation method and application thereof
CN120209451A
Flavor-retaining plastic multi-layer container
EP0824067A2
Multilayer thermoplastic structure
EP1173134A1
Multilayer structures, articles comprising the same, and methods of making multilayer structures
US20210276305A1